Alignment of N@C60 derivatives in a liquid crystal matrix. - Liu, G; Gimenez-Lopez, M; Jevric, M; Khlobystov, A; Briggs, G; Porfyrakis, K (2013)
The orientation of different N-substituted [N@C60]fulleropyrrolidine derivatives hosted in a nematic liquid crystal matrix has been studied by electron spin resonance spectroscopy. In this study, variations on the zero field splitting parameter of the guest species are employed as a means of determining their degree of orientation. Fulleropyrrolidines with more rigid N-substituents are preferentially oriented in the liquid crystal matrix, whereas those with less rigid substituents are almost randomly distributed. Additionally, the orientation of a C60 fullerene cage bearing a nitroxide radical has also been investigated in comparison.